A Control Effectiveness Estimator with a Moving Horizon Robustness Modification for Fault-Tolerant Hexacopter Control. Issue 1 (July 2017) - Niermeyer, Philipp; Pak, Mikhail; Lohmann, Boris
Abstract: Online estimation of control effectiveness in combination with appropriate controller reconfiguration is a promising method for introducing a certain fault-tolerance into a control system. The contribution of this paper is twofold. First, it investigates the observability of the parameters to be determined for a hexacopter; second, a novel approach is introduced which combines moving horizon estimator (MHE) and Lyapunov-based methods. Conventional and proposed estimators are tuned and validated to assess their performance. Ease of implementation along with beneficial error characteristics are the main strength of the presented nonlinear MHE-augmented Lyapunov-based estimator.